2015
DOI: 10.1111/hdi.12321
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after near drowning: The way from the beach to hemodialysis

Abstract: Acute kidney injury (AKI) occurs in many different situations and may have a variable prognosis influenced by clinical setting, underlying cause, and comorbidity. This is important because of the high mortality and morbidity risk affecting many people around the world. Near-drowning related AKI requiring hemodialysis is very seldom reported in literature. Although cardiovascular and respiratory disorders are more frequently seen after this entity, we aimed to emphasize this rare but dangerous complication in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The cases with severe isolated AKI after near-drowning are very seldom reported [5]. In another study, Alp A et al present a rare cause of AKI in a middle-aged man with hemodialysis [1]. Our case had AKI.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The cases with severe isolated AKI after near-drowning are very seldom reported [5]. In another study, Alp A et al present a rare cause of AKI in a middle-aged man with hemodialysis [1]. Our case had AKI.…”
mentioning
confidence: 54%
“…Although the typical flow diagram splits into prerenal, renal, and postrenal subgroups. Some of the clinical entities may not be defined within a specific subset, which is the case for AKI associated with near-drowning [1]. Only a small number of such cases have been reported.…”
mentioning
confidence: 99%
“…Two patients underwent CRRT because their creatinine levels increased by more than two-fold during the hospital stay, and the urine output was less than 0.3 mL/kg/h despite adequate fluid therapy. AKI in near drowning patients is caused by hypoxic renal injury, reduced renal blood flow, and systemic inflammatory response [17][18][19]. However, since patients who require CRRT are uncommon, AKI must be mild and is probably caused by acute tubular necrosis [8,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…AKI in near drowning patients is caused by hypoxic renal injury, reduced renal blood flow, and systemic inflammatory response [17][18][19]. However, since patients who require CRRT are uncommon, AKI must be mild and is probably caused by acute tubular necrosis [8,[17][18][19]. Unlike previous studies, we did not perform renal biopsy to differentiate the causes of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search revealed that AKI in seemingly well victims of near drowning is often diagnosed after a delay of a few days from the initial event. This is due to victims presenting late [3][4][5] or due to AKI not being evident or picked up during the immediate medical visit post drowning [6][7][8] and only detected the 2 nd time the victims re-attended. Summary of the cases is shown in Table 1.…”
Section: Year Of Publicationmentioning
confidence: 99%